An empirical research on the acceptance of sports social APP in China - Xia, Qianqian (My University, 2018)
In modern China, the national economy has been continuously upgraded to promote the exercise participation of all citizens. Meanwhile, the rapid development of mobile Internet technology has spawned a series of sports fitness applications, new forms of social interest continue to emerge, promoting the "sports + social" integration, resulting in a surge in sports social products. With the increasing researches in the field of user behavior, analyzing individuals’ psychological and behavioral characteristics when adopting information technology have become one of the hot topic that have attracted much attention in the field of information systems. At present, academic studies in the sports social industry have just started. However, researches which explore key influencing factors of sports social APP and innovations can improve its user experience is limited. This paper reviewed existing research in information technology and information system acceptance, based on previous, selected UTAUT as theoretical basis model, and introduces individual innovation, perceived cost and perceived entertainment as three external variables to build the sports social APP user adoption model concerning its the characteristics. An online quantitative questionnaire is employed in this paper to collect empirical data, after descriptive statistics of the 290 valid sample are presented, reliability and validity of the scale are tested with SPSS22.0, finally SmartPLS3.0 is used to evaluate the research model and examine the hypotheses put forward. The result indicates that: effort expectancy, social influence, facilitating conditions, individual innovation and perceived entertainment have positive impact on the adoption behavior. This paper analyzes the results of hypothesis concerning the characteristics of sports social APP, and puts forward recommendations for China sports social networking industry development and promotion.
Keywords: adoption behavior, UTAUT, empirical research, sports social